Analisis Hatarakikake No Bun Dalam Game Tears Of Themis - Nuzulli Galuh Citra Gayatri; Cuk Yuana (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstrak. Penelitian ini bertujuan untuk mengelompokkan hatarakikake no bun berdasarkan fungsinya yang ditemukan dalam Game Tears of Themis. Metode penelitian yang digunakan adalah metode deskriptif kualitatif dengan pendekatan sintaksis. Data penelitian diperoleh dari game Tears of Themis. Analisis dilakukan untuk mengidentifikasi fungsi-fungsi hatarakikake no bun yang muncul, termasuk fungsi meirei (perintah), irai (permohonan), kinshi (larangan), dan kany’uu (ajakan). Hasil penelitian menemukan 25 data. Hatarakikake no bun fungsi meirei ada 8 data. Hatarakikake no bun fungsi irai ada 8 data. Hatarakikake no bun fungsi kinshi ada 5 data. Sementara itu, hatarakikake no bun fungsi kan’yuu ada 4 data. Kata Kunci: hatarakikake no bun, fungsi, Tears of Themis. Abstract. This research aims to categorize hatarakikake no bun based on its function that found in Tears of Themis Game. The research method used is descriptive qualitative, with a syntactic approach. The data were obtained from the game Tears of Themis. The analysis was conducted to identify the functions of hatarakikake no bun that found in tears of themis, including meirei (command), irai (request), kinshi (prohibition), and kany'uu (invitation) functions. The research found 25 data. Hatarakikake no bun meirei function has 8 data. Hatarakikake no bun irai function has 8 data. Hatarakikake no bun kinshi function has 5 data. Meanwhile, there are 4 data of hatarakikake no bun kan'yuu function. Keywords: hatarakikake no bun, function, Tears of Themis.